Eeloscope—Towards a Novel Endoscopic System Enabling Digital Aircraft Fuel Tank Maintenance - Florian Heilemann; Alireza Dadashi; Kai Wicke (Aerospace, 2021)
In this research article, a novel endoscopic system, which is suited to perform a digital inspection of the aircraft wing fuel tanks, is introduced. The aim of this work is to specifically design and develop an assisting system, called `Eeloscope’, to allow accessing and diving through an aircraft kerosene tank in a minimally invasive matter. Currently, mechanics often suffer from the harsh working environment and the arduous maintenance duties within the tank. To address such challenges and derive a tailored solution, an adapted Design Thinking (DT) process is applied. The resulting system enables a fully digital inspection and generation of 3-dimensional structural inspection data. Consequently, devices such as the Eeloscope will facilitate a more efficient and continuous inspection of fuel tanks to increase the transparency regarding the condition of hardly accessible aircraft structures and provide a work relief for mechanics at the same time.